Corazones alemanes en Quirio – documental fotográfico - Guainazzo López, María Grazia (2020)
Deutsche Herzen in Quirio is a bilingual (German - Spanish) photographic documentary that shows, through more than 50 photographs, the story of the German Social Project "Chosica", which has as its protagonists the families of this town and the team that composes it. This work plays a role of aesthetic and social diffusion thanks to its storytelling approach. The development of this photobook went through a creative process that was divided into pre-production, production and post-production that will be detailed in this report.